2016
DOI: 10.1159/000445860
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Impacts of Serum CA-125 Levels, Pap Smear Evaluation, and Endometrial Sampling in Women with Endometrial Clear Cell Carcinoma

Abstract: Background: Endometrial clear cell carcinoma (ECCC) is a rare variant of endometrial cancer with an unfavorable prognosis. The aim of this study was to determine the relationships, if any, between preoperative serum cancer antigen 125 (CA-125) levels, the last Papanicolaou (Pap) smear, the results of endometrial biopsy and tumor histology, and disease-stage according to permanent histopathology. Materials and Methods: The data of 26 women with ECCC were collected from their medical records to compare demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Chao et al found that elevated serum CA125 levels usually indicate deep MI, extrauterine spread, positive PWC, lymph node metastasis, advanced-stage disease, and recurrence [ 17 ]. In line with the literature [ 18 ], one-third of the patients (46/144, 31.9%) in our cohort had elevated serum CA125 levels and 30 of 46 (65.2%) patients were diagnosed with stage III–IV disease. Compared to patients with early-stage disease, those with advanced-stage disease had a higher prevalence of positive LVSI, mixed histology, deep MI, positive PWC, and elevated serum CA125 levels ( p < 0.05).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Chao et al found that elevated serum CA125 levels usually indicate deep MI, extrauterine spread, positive PWC, lymph node metastasis, advanced-stage disease, and recurrence [ 17 ]. In line with the literature [ 18 ], one-third of the patients (46/144, 31.9%) in our cohort had elevated serum CA125 levels and 30 of 46 (65.2%) patients were diagnosed with stage III–IV disease. Compared to patients with early-stage disease, those with advanced-stage disease had a higher prevalence of positive LVSI, mixed histology, deep MI, positive PWC, and elevated serum CA125 levels ( p < 0.05).…”
Section: Discussionsupporting
confidence: 91%
“…Compared to patients with early-stage disease, those with advanced-stage disease had a higher prevalence of positive LVSI, mixed histology, deep MI, positive PWC, and elevated serum CA125 levels ( p < 0.05). However, Cetinkaya et al found that the prevalence of advanced-stage disease was significantly higher in patients with pure ECCC than in those with mixed histological subtypes ( p = 0.04) [ 18 ]. These results contradict the findings of this study.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 45 studies 19,20,23,25,29‐69 that were eligible for meta‐analysis and included a total of 6599 women who had been diagnosed with endometrial cancer. Most of the included studies were performed in North America (n = 21); the other studies were performed in Asia/Oceania (n = 13), Europe (n = 10), and Africa (n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…Coherent with the literature, the study demonstrated that elevated preoperative serum CA 125 level was an independent risk factor for survival. Also, high CA 125 is associated with extrauterine involvement and disseminated disease [27][28][29].…”
Section: Discussionmentioning
confidence: 99%